Julgamento perceptivo-auditivo e perceptivo-visual na identificação de produções gradientes em fricativas - Lima, Fernanda Leitão de Castro Nunes de [UNESP]; Berti, Larissa Cristina [UNESP]; Marino, Viviane Cristina de Castro [UNESP]; Fabbron, Eliana Maria Gradim [UNESP] (FapUNIFESP (SciELO), 2021)
PURPOSE: To analyze which method of judgment, auditory- perceptual (PAJ) of audios or perceptual-visual judgment (PVJ) (ultrasound images), is more sensitive to detect gradual productions between the class of deaf coronal fricatives and check if there is a correlation between these forms of judgment. METHOD: Audio and video files of language ultrasound (LUS) related to the production of the words frog and key, of 11 children, between 6 and 12 years old, with atypical speech production, were selected from a bank data and edited for judgments. After instruction and prior training, 20 judges should choose, immediately upon presentation of the stimulus (auditory or visual), one of three options arranged on the computer screen. In PAJ the options were: correct, incorrect or gradient production, while in PVJ the options were images corresponding to the production of [s], [∫] or undifferentiated. The presentation time of the stimuli and the reaction time were automatically controlled by the PERCEVAL software. RESULTS: PVJ provided a higher percentage of identification of gradient stimuli and a shorter reaction time in performing the task compared to PAJ, both statistically significant. Spearman's correlation test did not show statistical significance between PAJ and PVJ responses, nor for reaction time. CONCLUSION: PVJ using US images proved to be the most sensitive method for detecting gradient production in the production of fricatives [s] and [∫], and can be used as a complementary method to PAJ in speech analysis.

OBJETIVO: Analisar qual método de julgamento, perceptivo-auditivo (JPA) de áudios ou julgamento perceptivo-visual (JPV) (imagens ultrassonográficas), é mais sensível para detectar produções gradientes entre a classe das fricativas coronais surdas e verificar se há correlação entre essas formas de julgamento. MÉTODO: Arquivos de áudio e vídeo de ultrassonografia de língua (USL) relativos às produções das palavras “sapo” e “chave”, de 11 crianças, entre 6 a 12 anos de idade, com produção de fala atípica, foram selecionados de um banco de dados e editados para os julgamentos. Após instrução e treino prévio, 20 juízes deveriam escolher, imediatamente à apresentação do estímulo (auditivo ou visual), uma dentre três opções dispostas na tela do computador. No JPA as opções eram: produção correta, incorreta ou gradiente, enquanto no JPV as opções eram imagens correspondentes à produção de [s], de [∫] ou indiferenciada. O tempo de apresentação dos estímulos e o tempo de reação foram controlados automaticamente pelo software PERCEVAL. RESULTADOS: O JPV propiciou uma maior porcentagem de identificação dos estímulos gradientes e um menor tempo de reação na realização da tarefa comparativamente ao JPA, ambos estatisticamente significante. O teste de correlação de Spearman não mostrou significância estatística entre as respostas do JPA e JPV, nem para o tempo de reação. CONCLUSÃO: O JPV com o uso de imagens US mostrou-se o método mais sensível para a detecção da produção gradiente na produção de fricativas [s] e [∫], podendo ser utilizado como método complementar ao JPA na análise de fala.
Perceptive-auditive and perceptive-visual judgment in the identification of gradient productions in fricatives